Crimes digitais: o crime de estupro virtual e sua interpretação à luz do princípio da legalidade - Dorigon, Tais Ross (2024)
This work addresses the crime of virtual rape, a form of violence in the digital world, in light of principle of legality, given the wide divergence on the topic. The objective is to reflect on the legal challenges and ethics of virtual rape, examining the principle of legality in cyberspace and identifying the need to adapting the legal system to address these crimes in an ever-changing environment. The search includes a historical analysis of the crime of rape and cybercrime, seeking to understand their evolution and contemporary relevance. Methodologically, it is a deductive, descriptive and bibliographical research. It was found the need to strengthen the protection of victims in cyberspace, highlighting the urgency of legislative and judicial. The main challenge is the absence of a specific criminal law to classify virtual rape as crime, which, in light of the principle of legality, prevents the broad interpretation or application of the analogy, causing legal uncertainty.